Case Report: Creeping Growth in Lymphoplasmacyte-Rich Meningioma—A Radiologic Variant - Li, Jiuhong; Zan, Xin; Feng, Min; Deng, Xueyun; Zhang, Si; Liu, Wenke (Frontiers in Surgery, 2021)
Lymphoplasmacyte-rich meningioma (LRM) is a rare histologic subtype of meningioma. Creeping-growth pattern is uncommon in meningioma, and the mechanism is unclear. Here, we report a 44-year-old man presented with extremities weakness for 2 months and incontinence for 2 weeks. Head and neck MRI revealed diffuse creeping-growth nodular meningeal masses with skull base, tentorium, sella area, and C1-6 vertebral plane involvement. An operation was carried out, cervical and lower clivus part of the lesion was resected, but gross total resection could not be achieved due to the widespread lesions. Pathologic examination revealed the diagnosis of LRM. The patient is free from progression clinically 3 months postoperatively. We also conducted a systematic literature review about LRM with creeping-growth pattern. A total of only nine cases (including the present case) of creeping-growth LRMs were included and analyzed in terms of clinical manifestations, radiological features, treatment, and outcome. LRMs show a higher rate (7.5%) of creeping-growth pattern than other types of meningiomas. The average creeping length of all creeping-growth LRMs was 11.4 ± 10.9 cm (range, 3–30 cm). Most cases (66.7%) had obvious peritumoral edema. Total removal rate is low (33.3%), and two of them (22.2%) received biopsy, followed by steroids treatment (or further immunosuppressive drugs therapy) and radiotherapy. The recurrence rate is higher than conventional LRMs (22.2 vs. 11.3%), and one patient (11.1%) died 11 months after treatment. Creeping-growth pattern in LRM may be considered as a general radiologic variant. The recurrence rate is higher compared with LRM with round/swelling pattern. We speculated that the pathogenesis of creeping growth in LRM may be associated with damage of lymphatic systems of the central nervous system.